PERENCANAAN PENGELOLAAN SAMPAH TERPADU DI KELURAHAN SEMPAJA SELATAN KOTA SAMARINDA - Busyairi, Muhammad; Ramadhan, Justia Dhika; Wijayanti, Dyah Wahyu (Bumi Lestari; Vol 15 No 2 (2015))
Samarinda is the capital city of the province of East Borneo. The government needs todo a serious waste management, with the increasing number of residents in the Village ofSouth Sempaja Samarinda the solid waste generated will be growing therefore thedevelopment of alternative processing which is Integrated Waste TreatmentSites which aimsto reduce the rate of waste disposal and treatment that should be managed in the EndProcessing Site that can directly extend the life of the End Processing Site. The purpose ofthis study is to design the Integrated Waste Treatment Site in the Village of South Sempaja.Thisresearch is descriptive quantitative with garbage samples from South Sempaja Villageresidents. The stages of this research include the identification of the problem, gatheringsupporting data on South Sempaja Village, Unit Price of Material in Samarinda and findthe volume of waste generated by South Sempaja Community and divided according to theclassification of the house. Then the overall data analysis of the data collected.The volumeof the average generation of garbage in the Village of South Sempaja amounted to 1,46 L/person/day and average weight of garbage generation in the Village of South Sempajaamounted to 0,47 kg/person/day and Total area of Integrated Waste  Treatment Sites in theVillage of South Sempaja is 1.218,97 mand 157,25 m22, with details of the main components is 1.061,72 m area of   the supporting components and trucks that go into Integrated WasteTreatment Sites in the Village of South Sempaja are 5 trucks with a capacity of 12 m2
Keywords: Planning, Integrated Waste Treatment Site, Garbage, South Sempaja